Letter from Marianne and Viktor Homburger to Max Bredig, June 11, 1939 - Homburger, Marianne; Homburger, Viktor (1939)
Marianne Homburger (1903-1987) and Viktor Homburger (1888-1968) wish Max Bredig (1902-1977) happy birthday and provide updates on their life in Germany.
Keywords: Homburger, Marianne, 1903-1986; Bredig, Max Albert, 1902-1977; Homburger, Viktor, 1888-1968